Deciphering the fibrotic process: mechanism of chronic radiation skin injury fibrosis - Wang, Yiren; Chen, Shouying; Bao, Shuilan; Yao, Li; Wen, Zhongjian; Xu, Lixia; Chen, Xiaoman; Guo, Shengmin; Pang, Haowen; Zhou, Yun; Zhou, Ping (Frontiers in Immunology, 2024)
Radiation skin injury is a common complication in malignant tumor radiotherapy and negatively affects the quality of life of patients. This study begins by reviewing the pathological mechanisms from initial radiation exposure to fibrosis development. It also considers the interactions of key fibrosis-associated factors, particularly Transforming growth factor-beta (TGF-β), together with its related molecular signaling pathways. Additionally, the study explores the roles of immune mechanisms, including macrophages and lymphocytes, in the fibrotic process. Furthermore, we discuss the downstream effects of TGF-β, potential therapeutic targets, and the extent of TGF-β involvement in radiation-induced skin injury fibrosis. Finally, we consider the challenges and prospects of combining computational biology, bioinformatics, and multi-omics artificial intelligence for future research directions.